DISRESPECT FOR THE ONTOLOGICAL DIGNITY OF THE HUMAN PERSON IN A VALUE-FREE SOCIETY: THE CONTEMPORARY NIGERIAN EXPERIENCE - Professor Andrew F. Uduigwomen; Dr. Christopher A. Udofia (American Journals Publishing, 2023)
It is an indisputable fact that respect for the individual person is grossly depreciating in Nigeria. Philosophers of old did appreciate the value of the human person. Ancient philosophers such as Socrates, Plato and Aristotle celebrated the intellectuality of the human person, which they saw as the distinguishing feature of man in the hierarchy of beings. The patristic and medieval philosophers such as Boethius and Thomas Aquinas defined the human person as an individual substance of rational nature, which implies the irreplaceability and inviolability of the human person. In the modern period, Kant underscored the pre-eminence of the human person when he warned that no human person should be used as a means, but as an end in himself. In contemporary times, the 1948 Universal Declaration of Human Rights confirmed the philosophical conception of man as a being of ineluctable dignity. Experience has shown that in contemporary Nigeria the respect for human person has depreciated considerably. Cases of serious human abuses abound. The aim of this chapter is to explore the evolution of the idea of human dignity across historical epochs, the elements and occurrences of the ugly trend of violation of human dignity in Nigeria and the possible way out of this dehumanizing phenomenon.